Approaches to address common barriers to colorectal cancer screening in rural communities of the CDC’s colorectal cancer control program - Sonja Hoover; Meagan R. Pilar; Florence K. L. Tangka; Sujha Subramanian (Preventive Oncology & Epidemiology)
Introduction: We identified potential approaches to address barriers to colorectal cancer (CRC) screening in rural communities of award recipients from the Centers for Disease Control and Prevention’s Colorectal Cancer Control Program (CRCCP).Methods: Nine program managers and directors discussed approaches to address barriers to CRC screening. The programs served areas with rural communities and tribal reservations. Participants participated in five monthly web-based meetings and completed questionnaires regarding the use and usefulness of approaches. We conducted two focus groups with award recipients’ partners to validate the approaches.Results: Participants indicated that patient reminders, small media, and translated materials were useful in increasing uptake. There were six approaches that all programs used and agreed were useful for providers, including creating standard operating procedures and promoting stool-based testing. There was more variation on usefulness at the health system level, but all programs used and agreed standing orders for stool-based tests were useful.Discussion: Through discussions, questionnaires, and focus groups with participants, we found that many of the approaches to overcoming barriers in rural areas focused on aiding patients in accessing screening and automating procedures to mitigate the impacts of staff and provider turnover. Further evaluation can determine effective, sustainable and cost-effective approaches.